The impact of constraint induced movement therapy on brain activation in chronic stroke patients with upper extremity paralysis: An fMRI study. Issue 3 (September 2014) - Wen, Bo; Ma, Lin; Weng, Changshui
ABSTRACT This study is designed to explore the impact of constraint‐induced movement therapy (CIMT) on brain activation in chronic stroke patients with upper extremity paralysis and seek valuable predictors of recovery. Six chronic stroke patients with right hand dysfunction and nine healthy control subjects participated in the study. The patient's hand function was assessed by the Action Research Arm Test and statistical significance was determined by a paired Student's t‐tests. We conducted functional magnetic resonance imaging and analyzed the data using Analysis of Functional Neuroimages software. After CIMT, function of the affected right hand improved continuously with no deterioration of left hand function. The bilateral primary sensorimotor, primary somatosensory, and somatosensory association cortex were evidently activated in response to paretic right hand movement with a tendency to transfer from the ipsilateral hemisphere to the contralateral hemisphere. Remarkably, the corpus striatum, thalamus, and cerebellum showed persistently increased bilateral activation throughout the whole process. Bilateral extrapyramidal structures including corpus striatum, thalamus, and cerebellum exhibited activation at low levels in response to movement of the unaffected left hand. Our results indicated that the bilateral primary sensorimotor cortex is the most highly activated brain region during CIMT. Furthermore, the hyperactivity of extrapyramidal structures plays an important facilitating role during recovery and represents a good predictor of recovery. A gradual rebalance of the activation of the neural network between the two cerebral hemispheres and a return to normal conditions was seen, which may be a positive sign for recovery. © 2014 Wiley Periodicals, Inc. Int J Imaging Syst Technol, 24, 270–275, 2014